Effect of Electrolyte Fluid on Initial and Final Pulse Rate after 400x3 Sprints - Pertiwi, Clara Rindianti Putri; Yosika, Ghana Firsta; Laoan, Menard Ian (CV Media Inti Teknologi, 2025)
This research is an experimental descriptive research. The purpose of this study is to determine the effect of pocari electrolyte fluid with the difference between the initial pulse rate and the first set pulse. This study uses a sample of Sports Coaching Education students class of 2021. A total of 20 students are active. This research was conducted in the field of SSA Pontianak. Before taking the test, students warm up and measure their initial pulse for 60 seconds. Next, do a run, every 400m measure your pulse for 60 seconds and so on. The results showed that there was a significant change from the initial pulse rate to the set 1 pulse rate, which is known as the average initial pulse rate value of 15.60, and the average initial set value of 28.90. Even though they have drunk electrolyte fluids, so electrolyte drinks are only useful for replenishing the lost fluids but cannot anticipate the fluids that will be lost or lower the pulse rate during exercise.